2020
DOI: 10.1080/03612112.2020.1756591
|View full text |Cite
|
Sign up to set email alerts
|

Research Report

Abstract: This study describes the efforts of Hospital Pusrawi Sdn Bhd, Malaysia, to integrate local culture , religion , and standards of good nursing practices in the design of its nursing uniform from until. The study is based

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
0
0
Order By: Relevance
“…Multiple studies have demonstrated that Muslim medical professionals should prioritize the same gender and consider modesty when examining Muslim patients [21], [28]. Malay-Muslim nurses also wear Islamic-compliant uniforms, including long sleeves and headscarves [29].…”
Section: Discussionmentioning
confidence: 99%
“…Multiple studies have demonstrated that Muslim medical professionals should prioritize the same gender and consider modesty when examining Muslim patients [21], [28]. Malay-Muslim nurses also wear Islamic-compliant uniforms, including long sleeves and headscarves [29].…”
Section: Discussionmentioning
confidence: 99%
“…The textbook's authors generally present several cues and norms to distinguish male and female characters based on the textbook's origin, religions, cultures, or society (Lee & Mahmoudi-Gahrouei, 2020). There are typical gender cues or norms used for females' appearances or attributes, such as long hair, wearing skirts, and most related to pink color (Ainamo, 2021;Bideaux, 2019) or for Muslim females with their long sleeves, headscarves, and ankle-length skirts (Saidun et al, 2021). Meanwhile, males used to have shorter hair, wear trousers or pants, and blue.…”
Section: Literature Review Gender Representation In English Textbooksmentioning
confidence: 99%